Absennya Kajian Ekonomi Politik Media di Indonesia - Agus Sudibyo (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2000)
The rapid and deep changing of the media requires new approach in media studies in Indonesia. The cutently predominating positivism is inadequate. The article advocates the use of a critical political economy as an alternative approach to study media in Indonesia.